2017
DOI: 10.1590/1518-8345.1820.2876
|View full text |Cite
|
Sign up to set email alerts
|

Fertility rates and perinatal outcomes of adolescent pregnancies: a retrospective population-based study

Abstract: Objective:analyze trends in fertility rates and associations with perinatal outcomes for adolescents in Santa Catarina, Brazil. Methods:a population-based study covering 2006 to 2013 was carried out to evaluate associations between perinatal outcomes and age groups, using odds ratios, and Chi-squared tests. Results:differences in the fertility rate among female adolescents across regions and time period were observed, ranging from 40.9 to 72.0 per 1,000 in mothers aged 15-19 years. Adolescents had fewer prenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 20 publications
1
13
0
11
Order By: Relevance
“…Premature birth can be associated with several conditions like maternal age as some studies have shown that extreme ages (< 19 years and > 35 years) are associated with prematurity (7)(8) , as well as the level of education and antagonistic social-demographic conditions may also be associated with it (3) . Therefore, education and training are methods to promote knowledge and health practices to social changes.…”
Section: Discussionmentioning
confidence: 99%
“…Premature birth can be associated with several conditions like maternal age as some studies have shown that extreme ages (< 19 years and > 35 years) are associated with prematurity (7)(8) , as well as the level of education and antagonistic social-demographic conditions may also be associated with it (3) . Therefore, education and training are methods to promote knowledge and health practices to social changes.…”
Section: Discussionmentioning
confidence: 99%
“…While many population studies about SRH planning in LAC treat the region as one unit, the use of LARC varies widely between LAC countries (Haiti, El Salvador, Honduras and Nicaragua are classified as low- and lower-middle-income countries, while Argentina, Brazil, Colombia, Chile and Mexico are classified as high- or upper-middle-income countries (, last accessed 29 July 2017)) and is highly impacted by government programmes and country income level (Tsui et al , 2010; United Nations, 2015b). This is especially true in high-risk groups such as adolescents (Souza et al , 2017; Svanemyr et al , 2017; Villalobos et al , 2017) and low-income women in rural settings with limited access to healthcare (Schuck-Paim et al , 2016). There are millions of low-income women in the region who are socially and economically disadvantaged and have an unmet need for contraception, often resulting in higher rates of UP (Marston and Cleland, 2003; Sedgh et al , 2014).…”
Section: The Burden Of Up In Lacmentioning
confidence: 99%
“…Enferm. UFSM, Santa Maria, v10, p. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]2020 vidas presente e futura dos jovens pais podem determinar a desistência dos estudos e a inserção precária no mercado de trabalho, especialmente em grupos populacionais vulneráveis. 9,[12][13] A taxa global da gravidez na adolescência vem diminuindo no estrato de 15 a 19 anos e mantém tendência de estabilização entre meninas de 10 a 14 anos.…”
unclassified
“…quanto mais avançada a idade da mãe, mais adequado é o pré-natal. 9,19,[24][25] As demais variáveis analisadas (peso ao nascer, idade gestacional, tipo de parto e Índice a necessidade de uma atenção diferenciada, que aborde as especificidades desse grupo etário, além de ações educativas e preventivas. [9][10]30 Nessa perspectiva, estudos internacionais sobre a efetividade da intervenção em saúde estão sendo desenvolvidos, cujos resultados vêm apontando para uma educação sexual abrangente, envolvendo vários atores e espaços.…”
unclassified
See 1 more Smart Citation